Prevalence and Correlates of HIV Infection among Street Boys in Kisumu, Kenya. - Ariella Goldblatt; Zachary Kwena; Maureen Lahiff; Kawango Agot; Alexandra Minnis; Ndola Prata; Jessica Lin; Elizabeth A Bukusi; Colette L Auerswald (PLoS ONE)
Introduction Despite their perceived vulnerability to HIV, East African street youth have been neglected in HIV prevention research. We examined HIV seroprevalence and correlates of HIV infection in a sample of male street youth in Kisumu, Kenya. Methods We enrolled a street-recruited sample of 13-21 year old street youth. Participants completed a survey followed by voluntary HIV counseling and testing. Survey items included demographics, homelessness history, survival activities, sexual behavior and substance use. We examined the relationship between predictor variables, markers of coercion and marginalization and HIV. Results The sample included 296 males. Survival activities included garbage picking (55%), helping market vendors (55%), begging (17%), and working as porters (46%) or domestic workers (4%). Forty-nine percent of participants reported at least weekly use of alcohol and 32% marijuana. Forty-six percent of participants reported lifetime inhalation of glue and 8% fuel. Seventy-nine percent of participants reported lifetime vaginal sex, 6% reported lifetime insertive anal sex and 8% reported lifetime receptive anal sex. Twelve (4.1%; 95% CI: 2.3-7.0) participants tested positive for HIV. Of those, all had been on the street for at least one year and all had engaged in vaginal sex. Occupations placing youth at particular risk of coercion by adults, including helping market vendors (prevalence ratio (PR) = 8.8; 95% CI: 1.2-67.5) and working as domestic workers (PR = 4.6; 95% CI: 1.1-19.0), were associated with HIV infection. Both insertive anal sex (PR = 10.2; 95% CI: 3.6-29.4) and receptive anal sex (PR = 3.9; 95% CI: 1.1-13.4) were associated with HIV infection. Drug use, begging, and garbage picking were not associated with HIV infection. Conclusions Although HIV prevalence in our sample of street youth is comparable to that of similarly-aged male youth in Nyanza Province, our findings highlight behavioral factors associated with HIV infection that offer opportunities for targeted prevention among street youth in East Africa.